PENYULUHAN BELA NEGARA BAGI SISWA-SISWI SMPN 11 dan 13 MAGELANG GUNA MENINGKATKAN RASA NASIONALISME - Siswanto, Dwi Joko; Aries Basuki (PPM Sdirjianbang Akademi Militer, 2023)
The purpose of this community service is to provide state defense counseling to SMPN 11 and 13 Magelang students, with the hope of increasing a sense of nationalism among students. Counseling is carried out using lecture, discussion, and simulation methods. The results of this activity show that students gain a better understanding of the importance of defending the country and a sense of nationalism, and are also able to apply these values in everyday life.